Acupuncture Delays Cartilage Degeneration through Upregulating SIRT1 Expression in Rats with Osteoarthritis. (31st December 2021) - Liu, Hui; Zhang, Tingting; Liu, Min; Wang, Chunhong; Yan, Jinfeng
Abstract : Silent mating type information regulation 2 homolog 1 (SIRT1) has been reported to inhibit osteoarthritic gene expression in chondrocytes. Here, efforts in this study were made to unveil the specific role of SIRT1 in the therapy of acupuncture on cartilage degeneration in osteoarthritis (OA). Specifically, OA was established by the anterior cruciate ligament transection method in the right knee joint of rats, subsequent to which acupuncture was performed on two acupoints. Injection with shSIRT1 sequence–inserted lentiviruses was conducted to investigate the role of SIRT1 in acupuncture-mediated OA. Morphological changes and cell apoptosis in rat OA cartilages were examined by safranin-O staining and terminal deoxynucleotidyl transferase-mediated nick-end labeling (TUNEL) assay, respectively. The serum levels of tumor necrosis factor (TNF)- α and interleukin (IL)-2 in OA rats were assessed by enzyme-linked immunosorbent assay (ELISA). The expressions of SIRT1, cartilage matrix degradation-related proteins (matrix metalloproteinase (MMP)-9 and ADAMTS5), NF- κ B signaling-related markers (p-p65/p65 and p-I κ B α /I κ B α ), and cartilage matrix synthesis-related proteins (collagen II and aggrecan) in the OA cartilage were analyzed by western blot. As a result, acupuncture counteracted OA-associated upregulation of TNF- α, IL-2, cartilage matrix degradation-related proteins, and NF- κ B signaling-related markers, morphological damage, apoptosis, SIRT1 downregulation, and loss of cartilage matrix synthesis-related proteins in rat articular cartilages. SIRT1 silencing reversed acupuncture-induced counteractive effects on the aforementioned OA-associated phenomena (except apoptosis, the experiment regarding which under SIRT1 silencing was not performed). Collectively, acupuncture inhibited chondrocyte apoptosis, inflammation, NF- κ B signaling activation, and cartilage matrix degradation by upregulating SIRT1 expression to delay OA-associated cartilage degeneration.